Ethnobotany of vascular plants use, conservation and management practice in the homegardens by the people of Dawuro in Southwestern Ethiopia - Mathewos Agize; Zemede Asfaw; Sileshi Nemomissa; Tizazu Gebre (Journal of Ethnobiology and Ethnomedicine)
Abstract Background Homegardens (HGs) are well-time-honored traditional land use systems in small plots of land with purposely designed intricate structure and a mixture of planted vascular plants (VPs) for different purposes. Hence, the present study was initiated to investigate the ethnobotanical information of vascular plants of homegardens and their use, conservation and management practice by the people of Dawuro in southwestern Ethiopia. Methods A total of 162 farmer informants were selected and interviewed within a distance of < 2 km, 2–4 km and > 4 km between the natural forest and homegardens, and 0.8–1 km between the homegardens. Quadrats of three 5 m × 10 m were laid (except front yard) around each living houses. Shannon–Wiener diversity index was used for analysis of diversity. Results There were 345 vascular plants in the homegardens distributed in 252 genera and 79 families. The most frequently recorded plant families were Fabaceae with 38 (11%), Asteraceae 33 (10%), and Lamiaceae 26 (7.5%). The species richness recorded per homegardens ranged from 13 to 59. Ensete ventricosum, Persea americana, Colocosia esculenta, Coffea arabica, Solanum capsicoides, and Ocimum basilicum were the most frequently occurred species. The homegarden was enset-based agrobiodiversity system providing food, medicine and other uses where the highest, 290 species were for medicine. Men are responsible for planting and propagating large-sized plant species in the homegardens, while small-sized were managed by women and children. The α-diversity (H’) ranged from 1.4 to 3.4 and the gamma diversity was 4.2. Culture has positive effect on diversity however, the diversity of species is affected by distance from natural forest (x 2 = 14.825, df = 4, p = 0.005) at P < 0.05 level. Conclusion Awareness raising designed and executed by farmer experts and researchers focusing on managing homegarden is necessary to fill the observed gaps in knowledge and attitude of the new generation. The enset-based homegarden management knowledge and practice as well as avoiding the diseases and other constraints of enset should be given attention. Furthermore, decisions on avoiding the growth and management of invasive exotic plant species like eucalyptus tree in the homegardens have to be made.